Permeation of sumatriptan succinate across human skin using multiple types of self-dissolving microneedle arrays fabricated from sodium hyaluronate. (13th September 2016) - Wu, Dan; Katsumi, Hidemasa; Quan, Ying-shu; Kamiyama, Fumio; Kusamori, Kosuke; Sakane, Toshiyasu; Yamamoto, Akira
Abstract: Available formulations of sumatriptan succinate (SS) have low bioavailability or are associated with site reactions. We developed various types of self-dissolving microneedle arrays (MNs) fabricated from sodium hyaluronate as a new delivery system for SS and evaluated their skin permeation and irritation in terms of clinical application. In vitro permeation studies with human skin, physicochemical properties (needle length, thickness and density), and penetration enhancers (glycerin, sodium dodecyl sulfate and lauric acid diethanolamide) were investigated. SS-loaded high-density MNs of 800 µm in length were the optimal formulation and met clinical therapeutic requirements. Penetration enhancers did not significantly affect permeation of SS from MNs. Optical coherence tomography images demonstrated that SS-loaded high-density MNs (800 µm) uniformly created drug permeation pathways for the delivery of SS into the skin. SS-loaded high-density MNs induced moderate primary skin irritations in rats, but the skin recovered within 72 h of removal of the MNs. These findings suggest that high-density MNs of 800 µm in length are an effective and promising formulation for transdermal delivery of SS. To our knowledge, this is the first report of SS permeation across human skin using self-dissolving MNs.